The Spliceosome-Activating Complex: Molecular Mechanisms Underlying the Function of a Pleiotropic Regulator - Koncz, Csaba; deJong, Femke; Villacorta, Nicolas; Szakonyi, Dora; Koncz, Zsuzsa (Frontiers in Plant Science, 2012)
Correct interpretation of the coding capacity of RNA polymerase II transcribed eukaryotic genes is determined by the recognition and removal of intronic sequences of pre-mRNAs by the spliceosome. Our current knowledge on dynamic assembly and subunit interactions of the spliceosome mostly derived from the characterization of yeast, Drosophila, and human spliceosomal complexes formed on model pre-mRNA templates in cell extracts. In addition to sequential structural rearrangements catalyzed by ATP-dependent DExH/D-box RNA helicases, catalytic activation of the spliceosome is critically dependent on its association with the NineTeen Complex (NTC) named after its core E3 ubiquitin ligase subunit PRP19. NTC, isolated recently from Arabidopsis, occurs in a complex with the essential RNA helicase and GTPase subunits of the U5 small nuclear RNA particle that are required for both transesterification reactions of splicing. A compilation of mass spectrometry data available on the composition of NTC and spliceosome complexes purified from different organisms indicates that about half of their conserved homologs are encoded by duplicated genes in Arabidopsis. Thus, while mutations of single genes encoding essential spliceosome and NTC components lead to cell death in other organisms, differential regulation of some of their functionally redundant Arabidopsis homologs permits the isolation of partial loss of function mutations. Non-lethal pleiotropic defects of these mutations provide a unique means for studying the roles of NTC in co-transcriptional assembly of the spliceosome and its crosstalk with DNA repair and cell death signaling pathways.